Engineering gold-silver nanoclusters (Au-Ag NCs) for antimicrobial application - Nasaruddin, Ricca Rahman; Wan Salim, Wan Wardatul Amani; Arzmi, Mohd Hafiz (2020)
The advancement of nanoscience and nanotechnology has continuously improved the fabrication and characterization of gold nanoparticles (Au NPs). Au NPs have shown intriguing physicochemical properties and promising biomedical applications such as antimicrobial agents, drug delivery, cancer therapy, bioimaging, biosensor, etc. However, the high cost of gold has lowered its commercial feasibility and practical application. Therefore, by reducing the size of Au NPs to the ultrasmall nanoclusters (NCs) which is less than 3 nm and alloying the Au NCs with other cheaper metal such as silver (Ag), the amount of gold needed can be reduced and the economic feasibility of the bimetallic gold-silver nanoclusters (AuAg NCs) can be increased. Interestingly, in our study, it was found that the bimetallic Au-Ag NCs protected by biocompatible peptides (i.e., glutathione) have better antimicrobial activity towards gram-positive bacteria (i.e., Staphylococcus aureus) and gram-negative bacteria (i.e., Escherichia coli) than monometallic Au NCs and even better than the monometallic Ag NCs, indicating that there could be synergistic effects between Au and Ag in the bimetallic AuAg NCs. The AuAg NCs also showed fluorescent property which promotes other biomedical applications such as bioimaging and theranostic. As this project is still ongoing, more experiments will be done to get better insights on the physicochemical properties, antimicrobial mechanism and biocompatibility of the bimetallic AuAg NCs.